PWE-053 Outcomes of anti-tnf versus vedolizumab therapy for ulcerative colitis: the leeds experience. (17th June 2017) - Johnston, AJ; Lenti, M; O'Connor, A; Selinger, C; Ford, AC; Hamlin, PJ
Abstract : Introduction: Two groups of biological therapies are licensed and approved by NICE for the management of moderate to severe UC in the UK. The anti-TNF drugs, Infliximab (IFX), Adalimumab (ADA) and Golimumab and the α4β7 anti-integrin Vedolizumab (VDZ). As there are no published head-to-head RCTs comparing the efficacy and safety of these drugs for UC, we aim to compare the outcomes for all patients treated with biological therapy for UC in our unit of 3000 IBD patients. Method: Anti-TNF or VDZ has been used routinely for UC maintenance therapy in Leeds since Oct 2015. We use biosimilar IFX as our first line anti-TNF, ADA for patients who prefer SC over IV therapy and VDZ for anti-TNF failures or contraindications. Acute severe colitis cases were excluded. We prospectively collected data on demographics and clinical outcomes over a 9 month period. Response and remission at 3 months were defined according to Mayo scores or physician global assessment (PGA) and compared using the Chi-squared test. Results: A total of 36 (20 female) patients received biological therapy for UC in this period (17 IFX, 6 ADA, 13 VDZ). Baseline results for IFX:ADA:VDZ respectively are; mean age (years) 38, 30, 41; disease duration (months) 92.8, 23.4, 54; mean weight (kg) 74, 80, 81; mean steroid dose (mg) 10.5, 1.6, 15; and thiopurine use 59%, 33%, 62%. Mayo scores at baseline were 6.4, 7.3, 7 or with endoscopy sub-scores 8.5 (n=14), 9.5 (n=2), 9 (n=8). 17/17 (100%) IFX patients were given the drug first line compared to 4/6 (67%) ADA and 2/13 (15%) VDZ. VDZ was used first-line in 1 case of MS and 1 of possible latent TB. After 3 months of IFX therapy 1 dose escalated, 3 switched to ADA due to low drug levels with high antibodies and 2 had treatment withdrawn due to infusion reactions. 50% of ADA patients dose escalated by 3 months. There were 4 colectomies in the VDZ group, all had previously failed ≥1 anti-TNF therapy. There was no significant difference in response (p=0.17) and remission (p=0.62) rates between IFX and VDZ. Conclusion: Anti-TNF and VDZ therapies are safe and effective in the management of UC. Whilst patient numbers were small 50% of ADA patients dose escalated, this is of particular note considering the relative cost of these therapies. VDZ response and remission rates of 69% and 38% are encouraging in this largely anti-TNF failure cohort, however more data on cost-effectiveness of anti-TNF versus VDZ first-line are required. Disclosure of Interest: A. Johnston: None Declared, M. Lenti: None Declared, A. O'Connor: None Declared, C. Selinger Conflict with: Warner Chilcott, Abbvie, Conflict with: Warner Chilcott, Dr Falk, Abbvie, Takeda, Janssen, Conflict with: Warner Chilcott, Dr Falk, Abbvie, MSD, Takeda, A. Ford: None Declared, P. Hamlin Conflict with: Abbvie, Dr Falk, Ferring, Janssen, MSD, Otsuka, Takeda Warner Chilcottee